Electrogram transition patterns in left bundle branch pacing: a case report - Jiabo Shen; Longfu Jiang; Hao Wu; Hengdong Li (BMC Cardiovascular Disorders)
Abstract Introduction Left bundle branch (LBB) pacing (LBBP) demonstrates clinical potential but faces challenges in confirming selective capture via dynamic electrogram (EGM) criteria. Case report A 69-year-old male with a complete atrioventricular block underwent LBBP implantation. Real-time EGM monitoring (high-pass/low-pass filters: 200/500 Hz) revealed an abrupt shortening of stimulus-to-V6 R-wave peak time (Sti-V6 RWPT) from 87 to 69 ms during lead deployment, indicating a transition from septal pacing to LBBP. Output reduction (1.6 V → 1.5 V/0.5 ms) eliminated myocardial excitation notches, yielding isoelectric EGMs confirming selective LBB capture. Further output reduction (1.4 V → 1.3 V/0.5 ms) prolonged Sti-V6 RWPT to 90 ms with an isoelectric interval, suggesting fascicular-level conduction delay. Conclusion This case report illustrates the electrophysiological features of a diseased conduction system via dynamic EGM analysis, despite technical limitations such as signal artifacts. While EGM morphological patterns assist in differentiating pacing modalities, further validation of these electrophysiological observations is necessary.